2015
DOI: 10.1002/ece3.1767
|View full text |Cite
|
Sign up to set email alerts
|

Complex metacommunity structure for benthic invertebrates in a low‐diversity coastal system

Abstract: The majority of studies in metacommunity ecology have focused on systems other than marine benthic ecosystems, thereby providing an impetus to broaden the focus of metacommunity research to comprise marine systems. These systems are more open than many other systems and may thus exhibit relatively less discrete patterns in community structure across space. Metacommunity structure of soft‐sediment benthic invertebrates was examined using a fine‐grained (285 sites) data set collected during one summer across a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 68 publications
2
32
0
Order By: Relevance
“…In order to put our resuspension potential measures to a context, we converted our results of erosion threshold to critical friction velocities (1.96–2.84 cm s −1 for “muddy” sediments and 2.11–3.73 cm s −1 for “sandy” sediments). These values are in the same range as estimated friction velocities in previous studies from the area (1.25–3.58 cm s −1 , Valanko ). Hydrodynamic forcing in the study area is regulated by upwelling and wind‐wave events (Haapala ; Lehmann & Myrberg ) and previous studies have shown that resuspension is a frequent phenomenon in the area (Valanko et al ).…”
Section: Discussionsupporting
confidence: 84%
“…In order to put our resuspension potential measures to a context, we converted our results of erosion threshold to critical friction velocities (1.96–2.84 cm s −1 for “muddy” sediments and 2.11–3.73 cm s −1 for “sandy” sediments). These values are in the same range as estimated friction velocities in previous studies from the area (1.25–3.58 cm s −1 , Valanko ). Hydrodynamic forcing in the study area is regulated by upwelling and wind‐wave events (Haapala ; Lehmann & Myrberg ) and previous studies have shown that resuspension is a frequent phenomenon in the area (Valanko et al ).…”
Section: Discussionsupporting
confidence: 84%
“…This together with the subsequent analyses of turnover and clumping in the EMS approach indicated a quasi-Clementsian structure [28] where partly overlapping distribution ranges of species shifted along this gradient indicating species sorting in the gradient. Such a pattern has recently been reported for invertebrates in other estuarine environments [26]. It cannot be ruled out, however, that some of the highly significant clumping is due to some truncation of the salinity gradient (see [28]) as the full gradient in the area, relevant for species with marine affinity, goes from > 30 to ca.…”
Section: Discussionsupporting
confidence: 63%
“…Then objective criteria based on coherence, turnover, and boundary clumping were used to assess the correspondence of the empirical data set with each of the hypothetical idealizations of species distribution ( i . e ., checkerboard, nested, evenly spaced, Gleasonian, or Clementsian patterns) [27,28,26]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the variation in benthic community structure in our examined study area has been suggested to be a result of similar responses of species’ to an underlying environmental gradient across sites (Valanko et al. ). How trait modalities interact is an important avenue for new research.…”
Section: Discussionmentioning
confidence: 90%